(untitled) (El-Wahat Journal for Research and Studies, 2021)
There Is No Doubt That The Topic Of Preparing The Field And The Development Of Land As A Concept And A Work Program Has Become The Top Priority And The Issues That Concern Most Countries, Believing That It Is The Only Way To Take Its Place Within The International Community, Which Has Forced The State To Develop Its Economic And Social Structure. The Agricultural Sector, Both Pastoral And Agricultural, In The State Of The Gang In Mauritania, Has Been Identified In The Study The Current Situation Of This Sector, Which Depends On The Majority Of The Population In Rural Mauritania, And Reached Important Results For Development Keywords - The Agricultural Sector - Agriculture - Development - Agricultural Development - Rural Areas